2007
DOI: 10.1128/aem.01947-06
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus neoformans Can Utilize the Bacterial Melanin Precursor Homogentisic Acid for Fungal Melanogenesis

Abstract: Cryptococcus neoformans melanizes in the environment and in mammalian tissues, but the process of melanization in either venue is mysterious given that this microbe produces melanin only from exogenous substrates. Understanding the process of melanization is important because melanization is believed to protect against various stresses in the environment, including UV radiation, and pigment production is associated with virulence. Melanization in C. neoformans requires the availability of diphenolic precursors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
10

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 15 publications
1
81
0
10
Order By: Relevance
“…The x axis represents the diameter size distribution of the GalXM particles measured in nanometers. The y axis corresponds to the percent intensity of weighted sizes (14). Note that there is no panel for GalXM from cap67 grown in minimal medium because we were unable to recover sufficient polysaccharide for this type of analysis in those conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The x axis represents the diameter size distribution of the GalXM particles measured in nanometers. The y axis corresponds to the percent intensity of weighted sizes (14). Note that there is no panel for GalXM from cap67 grown in minimal medium because we were unable to recover sufficient polysaccharide for this type of analysis in those conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Melanins are also broadly distributed among eukaryotic microorganisms, including fungi and protozoa (70,79 (4,29,33,42,45,55,64,90,102). Among the eukaryotic microbes, endogenous HGA-melanin production is thus far limited to the fungi Aspergillus nidulans and Yarrowia lipolytica (13,36), although it has recently been shown that the fungus Cryptococcus neoformans can use HGA produced by others to achieve melanization (38). Thus, L. pneumophila, along with P. aeruginosa and V. cholerae, is one of the few known producers of HGAmelanin that is also a significant human pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…As these pigments are formed in the brain after infection, a pathogenic neuromelanin is formed using brain compounds [122] and that increases the virulence of the infection. On the other hand, C. neoformans is also able to synthesize pyomelanin derived from a fungal metabolite, homogentisic acid (HGA, Figure 1(h)) [123]. This route gives place to a melanin in the form of "ghost-" like hydrophobic particles, fluorescent under a variety of wavelengths resistant to degradation by strong acids that could increase the virulence of this fungus.…”
Section: New Journal Of Sciencementioning
confidence: 99%